Development of offshore wind energy of Ukraine in the Sea of Azov: the geographical aspect - Popovych, Nataliia; Peresadko, Vilina; Dzhym, Daria (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2021)
Formulation of the problem. Ukraine’s energy sector is import-dependent, and one of the country’s sustainable development goals until 2030 is to ensure access to affordable, reliable, sustainable and modern energy sources. The wind potential of the mainland of our country has been thoroughly studied, so the focus of our interest is water areas, which are promising for the development of offshore wind energy. Offshore wind farms in Ukraine could improve the environmental situation and considerably contribute to the decarbonization of domestic energy. That is why the study considers the opportunity of offshore wind farms installation in the Sea of Azov. Methods. The analysis of literary and cartographic sources has been carried out. Mathematical methods have been used to calculate energy indicators. Using geoinformation modeling, taking into account limiting factors, suitable for the installation of offshore wind farms areas have been identified in the Sea of Azov. The purpose of the article is to geographically analyze the wind energy potential of the Sea of Azov with further assessment of the suitability of areas for the offshore wind farms location. Results. Our research has shown that the installation of offshore wind farms is appropriate in the Sea of Azov, because many areas are characterized by average annual wind speed above 6 meters per second. The most promising areas are the northern and northeastern coasts, where wind speed at different altitudes ranges from 8 to 9.3 meters per second. At altitudes of 50, 100 and 200 m, under the action of limiting factors, the most promising for offshore wind turbines areas are reduced by 8–22%. As considered limiting factors (territorial waters, nature protection objects, settlements and airports) have identical influence regardless of height, it is more effective to install wind turbines with a tower height of more than 100 m in the waters of the Sea of Azov. Interdisciplinary research is needed for the final answer on the effectiveness of offshore wind turbines in the Sea of Azov. Scientific novelty and practical significance. The results of the analysis of the wind energy potential of the Sea of Azov have been given, the tendency of its growth from the west to the east has been revealed. Attention has been paid to the method of geoinformation modeling of the location of offshore wind farms taking into account limiting factors. Maps of wind speed, potential of electricity generated by a single wind turbine and suitability of areas of the Sea of Azov for the location of offshore wind farms at an altitude of 200 m above sea level have been presented. These data can be used by designers of wind energy facilities as a basis for determining the optimal power of wind turbines and the type of energy for a particular area of the Sea of Azov.